Improvement Model to Increase the Order Fulfillment Rate in a Peruvian SME Food Company Using SMED, Kanban and Standard Work - Flores Pérez, Alberto Enrique (2023)
The food industry is one of the main players in the development of the Peruvian economy. However, new challenges and changes are continuously presented in order to better adapt to the needs of the consumer, and in the process to overcome these challenges, problems such as poor process management, long production times and low efficiency are often encountered. In this way, the aforementioned drawbacks generate as a consequence a low rate of order fulfilment, which generates a negative economic impact. In this research, a model using Lean manufacturing tools such as SMED, Kanban and Standard Work was proposed. The model mainly seeks to increase to 95% the current order fulfilment rate in a Peruvian SME food company, which after the implementation of the model obtained a value of 95.86%. In addition, other improvements were obtained such as a 14.45% reduction in penalties, a 19% reduction in the main process (pack arming) cycle time and a 10.33% reduction in moving times. These results proved the effectiveness of the proposed model, which was validated through a simulation in the Arena 16 Software.